Recent applications of immunomodulatory biomaterials for disease immunotherapy. Issue 6 (23rd May 2022) - Dai, Huaxing; Fan, Qin; Wang, Chao
Abstract: Immunotherapy is used to regulate systemic hyperactivation or hypoactivation to treat various diseases. Biomaterial‐based immunotherapy systems can improve therapeutic effects through targeted drug delivery, immunoengineering, etc. However, the immunomodulatory effects of biomaterials themselves cannot be neglected. In this review, we outline biomaterials with immunomodulatory functions discovered in recent years and their applications in disease treatment. These biomaterials can treat inflammation, tumors, or autoimmune diseases by regulating immune cell function, exerting enzyme‐like activity, neutralizing cytokines, etc. The prospects and challenges of biomaterial‐based modulation of immunotherapy are also discussed. Abstract : Understanding the immunomodulatory functions of biomaterials themselves is critical for developing safe and effective immunotherapeutic platforms. This review summarizes some representative biomaterials with immunomodulatory functions discovered in recent years and their applications in therapy for inflammation, tumor, and autoimmune diseases, and discusses the challenges for the future development of biomaterials.